Eryptosis as a New Insight in Malaria Pathogenesis - Scovino, Aline Miranda; Totino, Paulo Renato Rivas; Morrot, Alexandre (Frontiers in Immunology, 2022)
Eryptosis is a programmed cell death-like process that occurs in red blood cells. Although the red blood cells are anucleated, there are similarities between eryptosis and apoptosis, such as increased calcium efflux, calpain activation, phosphatidylserine exposure, cell blebbing and cell shrinkage. Eryptosis occurs physiologically in red blood cells, as a consequence of the natural senescence process of these cells, but it can also be stimulated in pathological situations such as metabolic syndromes, uremic syndromes, polycythemia vera, anemias such as sickle cell anemia and thalassemia, and infectious processes including Plasmodium infection. Infection-induced eryptosis is believed to contribute to damage caused by Plasmodium, but it’s still a topic of debate in the literature. In this review, we provided an overview of eryptosis mechanisms and its possible pathogenic role in malaria.